CONTRIBUTION TO THE DEVELOPMENT OF ART EDUCATION OF GALICIAN ARTISTS - O. Volynska (Освітній вимір, 2022)
The importance of art and pedagogical in heritage of Halychyna for the development and reform of modem art school in Ukraine has been analyzed of the author.